Biogas production from sewage sludge by anaerobic digestion - Omar Mohammed Hassan; Hamid Salman khamis (Tikrit Journal of Pure Science)
Some plant residues with digested sewage sludge was used for biogas production at 35o C, and a retention time of 30 days; has been shown that possibility of producing biogas from primary sludge, with daily production rate about 77.41 - 95.52 cm3 biogas . day-1, and the average yield production between 89.22 - 113.88 cm3 biogas per g volatile solids added. And that the results of the gas chromatography analysis, show the presence of a acceptance percentage of methane within the contents of biogas between 52.6 - 59.2%. with surpass of wheat straw media over other plant residues media in biogas production and methane content rate. The study reached to that anaerobic digestion process with batch culture efficient in organic treatment presence in swage sludge with plant residues with good quantity of biogas (methane) production.